AB0052 Increased peripheral CD8+ T cell responses in sle by low-dose IL-2 treatment. (15th June 2017) - Zhang, R; He, J; Sun, X; Zou, Y; Gan, Y; Li, Z
Abstract : Background: CD8+ T cell responses to viral pathogens is crucial for the prompt resolution of acute infections. SLE patients are more likely to have infections due to suppression of immune system by long-term glucocorticoid and immunosuppressive agent intake. Our previous study showed that low-dose IL-2 is effective in SLE. Objectives: The present study is to evaluate the potential anti-infection effect of low-dose IL-2 in refractory SLE patients. Methods: Nine refractory SLE patients and 9 health controls (HCs) were recruited three cycles of 1 million IU recombinant human IL-2 (rhIL-2), administered subcutaneously every other day for 2 weeks, followed by a 2-week break. The disease activitise were evaluated by rheumatologist. The frequencies of T cell subsets were assayed by flow cytometry. Virus-specific CD8 T cells responses were determined based on TNF-a, IFN-g and Grazmy B producing CD8 T cells upon CMV-EBV-Flu (CEF) viral peptide pool stimulation and subsequent intracellular staining. Results: Most patients showed good clinical responses after three cycles of low-dose IL-2 treatment. Clinical improvement was observed in SIR-4 response, improved complement 3 and 4 serum level and decreased anti-ds-DNA serum level. Functional profiling of CD8 T cells in low-dose IL-2 treated patients revealed an increased in the frequencies of CEF viral peptide specific TNF-a + and Grazmy-B + CD8 T cells. Moreover, low-dose IL-2 treated patients showed stronger antigen-specific response demonstrated by an increased stimulated/non-stimulate TNF-a-producing CD 8 T cells proliferation fold. Compared with HCs, SLE patients showed significantly lower frequencies of CEF specific Grazmy-B producing CD8 T cell, and treatment with low-dose IL-2 significantly increased the frequency of these Grazmy-B + CD8 T cells in SLE patients. Conclusions: Low-dose IL-2 treatment was effective and safe in refractory SLE patients. Virus-specific antigen-specific CD8 T cell response could be enhanced upon this treatment which might be potentially valuable in anti-infection in SLE. References: Bilate AM, Lafaille JJ. Induced CD4+Foxp3+ regulatory T cells in immune tolerance. Annu Rev Immunol. 2012;30:733–58. Blattman JN, Grayson JM, Wherry EJ, Kaech SM, Smith KA, Ahmed R. Therapeutic use of IL-2 to enhance antiviral T-cell responses in vivo. Nat Med. 2003;9(5):540–7. Palucka K, Banchereau J. Diversity and collaboration for effective immunotherapy. Nat Med. 2016;22(12):1390–1. Acknowledgements: We thank Pro. Xin Lin for valuable suggestions to this manuscript. The research in the laboratory was funded by grants from the NSFC (21010000237, NSFC by Pro. Jing He and Zhanguo Li. Disclosure of Interest: None declared